2020
DOI: 10.3389/fphys.2020.00921
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Bridges and Sarcomeric Non-cross-bridge Structures Contribute to Increased Work in Stretch-Shortening Cycles

Abstract: Stretch-shortening cycles (SSCs) refer to the muscle action when an active muscle stretch is immediately followed by active muscle shortening. This combination of eccentric and concentric contractions is the most important type of daily muscle action and plays a significant role in natural locomotion such as walking, running or jumping. SSCs are used in human and animal movements especially when a high movement speed or economy is required. A key feature of SSCs is the increase in muscular force and work durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 93 publications
2
38
0
Order By: Relevance
“…Muscle preparation, storage, and activation techniques for permeabilized single muscle fibers were in line with Tomalka et al (2017Tomalka et al ( , 2020. Briefly, experiments were performed on glycerinated skinned single fiber segments from soleus muscles of six freshly killed female Wistar rats (age: 3 months, weight: 428-520 g, cage-sedentary, 12-12 h light: dark cycle, housingtemperature: 22 • C).…”
Section: Preparation Handling and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle preparation, storage, and activation techniques for permeabilized single muscle fibers were in line with Tomalka et al (2017Tomalka et al ( , 2020. Briefly, experiments were performed on glycerinated skinned single fiber segments from soleus muscles of six freshly killed female Wistar rats (age: 3 months, weight: 428-520 g, cage-sedentary, 12-12 h light: dark cycle, housingtemperature: 22 • C).…”
Section: Preparation Handling and Experimental Setupmentioning
confidence: 99%
“…An SSC-effect of about 30% of work enhancement relative to pure shortening was reported for slow stretch-shortening velocities [about 10% maximum shortening velocity (v 0 )] and long muscle fiber lengths [2.4-3.3 µm, descending limb of the force-length relation (F-lr)] of skinned rabbit soleus muscle fibers (Fukutani et al, 2017a;Fukutani and Herzog, 2019). Tomalka et al (2020) demonstrated that the SSC-effect in skinned rat soleus muscle fibers also occurs in the more physiological working range (plateau region and ascending limb of the F-l-r) at fast contraction velocities (∼85% v 0 ). Mechanisms related to activation dynamics, reflex activity, and elastic recoil from tendons-as discussed for in vivo muscle action-cannot be responsible for the SSC-effect in skinned muscle fiber experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an increase in cross-bridge recruitment would not occur in the stretch phase of the SSCs but would have to occur in the shortening phase. A plausible explanation for a reduced inhibition of cross-bridge formation during the shortening phase of SSC was suggested by Fortuna et al (2019) and further supported by Tomalka et al (2020) . These authors argued that in pure shortening contractions, work is produced primarily by cross-bridges, while in SSC contractions, a substantial amount of the shortening work is produced by the recoil of the passive structures that elongated during the stretch phase of the SSCs ( Fortuna et al, 2019 ).…”
Section: Discussionmentioning
confidence: 78%
“…Thus, it is reasonable to assume that contributions to the SSC effect not produced by cross-bridges, for example titin, become more prominent in reduced force states. This hypothesis has been tested using a myosin inhibitor, blebbistatin, and it was found that the SSC effect was still observed even though the active force was substantially decreased ( Tomalka et al, 2020 ). Similarly, temperature may affect the SSC effect.…”
Section: Factors Modulating the Contribution On The Ssc Effectmentioning
confidence: 99%